Pluronic-F-127-passivated SnO2 nanoparticles derived by using Polygonum cuspidatum root extract: synthesis, characterization, and anticancer properties - Alzahrani, Badr; Elderdery, Abozer Y.; Alzerwi, Nasser A. N.; Alsrhani, Abdullah; Alsultan, Afnan; Rayzah, Musaed; Idrees, Bandar; Rayzah, Fares; Baksh, Yaser; Alzahrani, Ahmed M.; Subbiah, Suresh K.; Mok, Pooi Ling (MDPI, 2023)
Nanotechnology has emerged as the most popular research topic with revolutionary applications across all scientific disciplines. Tin oxide (SnO2) has been gaining considerable attention lately owing to its intriguing features, which can be enhanced by its synthesis in the nanoscale range. The establishment of a cost-efficient and ecologically friendly procedure for its production is the result of growing concerns about human well-being. The novelty and significance of this study lie in the fact that the synthesized SnO2 nanoparticles have been tailored to have specific properties, such as size and morphology. These properties are crucial for their applications. Moreover, this study provides insights into the synthesis process of SnO2 nanoparticles, which can be useful for developing efficient and cost-effective methods for large-scale production. In the current study, green Pluronic-coated SnO2 nanoparticles (NPs) utilizing the root extracts of Polygonum cuspidatum have been formulated and characterized by several methods such as UV–visible, Fourier transform infrared spectroscopy (FTIR), energy dispersive X-ray (EDAX), transmission electron microscope (TEM), field emission-scanning electron microscope (FE-SEM), X-ray diffraction (XRD), photoluminescence (PL), and dynamic light scattering (DLS) studies. The crystallite size of SnO2 NPs was estimated to be 45 nm, and a tetragonal rutile-type crystalline structure was observed. FESEM analysis validated the NPs’ spherical structure. The cytotoxic potential of the NPs against HepG2 cells was assessed using the in vitro MTT assay. The apoptotic efficiency of the NPs was evaluated using a dual-staining approach. The NPs revealed substantial cytotoxic effects against HepG2 cells but failed to exhibit cytotoxicity in different liver cell lines. Furthermore, dual staining and flow cytometry studies revealed higher apoptosis in NP-treated HepG2 cells. Nanoparticle treatment also inhibited the cell cycle at G0/G1 stage. It increased oxidative stress and promoted apoptosis by encouraging pro-apoptotic protein expression in HepG2 cells. NP treatment effectively blocked the PI3K/Akt/mTOR axis in HepG2 cells. Thus, green Pluronic-F-127-coated SnO2 NPs exhibits enormous efficiency to be utilized as an talented anticancer agent.